2019
DOI: 10.1007/s00701-019-03832-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of choroid plexus tumors—an institutional experience

Abstract: BackgroundChoroid plexus tumors are rare entities. Resection is the mainstay of treatment in grade I and grade II tumors and adjuvant treatment is usually reserved for the less frequent choroid plexus carcinoma (CPC). Outcome is not only related to their histological grade but also dependent on their size, location, and presence of often multifactorial disturbances of cerebrospinal fluid (CSF) circulation.MethodsRetrospective analysis of 36 consecutive patients operated on a choroid plexus tumor at our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 49 publications
2
64
1
12
Order By: Relevance
“…We encountered a higher rate of infratentorial CPT location (75%) in our patient population over the last decade, which is contrary to the rates reported in prior studies and our own prior experiences [10,14,15]. We did not have any CPC in our cohort; however, the incidence of CPC among CPTs of all locations is approximately 11% in prior studies [2], and its infratentorial occurrence is exceedingly uncommon [16]. However, others reported anaplastic choroid plexus carcinoma is a tumor with a predilection for the posterior fossa of infants [17].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We encountered a higher rate of infratentorial CPT location (75%) in our patient population over the last decade, which is contrary to the rates reported in prior studies and our own prior experiences [10,14,15]. We did not have any CPC in our cohort; however, the incidence of CPC among CPTs of all locations is approximately 11% in prior studies [2], and its infratentorial occurrence is exceedingly uncommon [16]. However, others reported anaplastic choroid plexus carcinoma is a tumor with a predilection for the posterior fossa of infants [17].…”
Section: Discussioncontrasting
confidence: 94%
“…Choroid plexus tumors (CPTs) are rare intraventricular tumors of neuroectodermal origin. CPTs occur predominantly in the lateral ventricle in children in contrast with adults who have primarily infratentorial lesions [1,2]. Choroid plexus tumors are classified by the World Health Organization (WHO) as choroid plexus papillomas (CPP) (WHO grade 1), atypical choroid plexus papillomas (aCPP) (WHO grade 2), and choroid plexus carcinomas (CPC) (WHO grade 3) [3].…”
Section: Introductionmentioning
confidence: 99%
“…As in humans, the main intraoperative complication in our case was bleeding from the CPT ( 8 ). It was controlled with thermocoagulation and specific anticoagulation materials ( 8 , 19 ). Observation is most critical in the 24 h following surgery, especially in cases of intraventricular tumor removal ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the human data, total resection is the most effective treatment for CPTs, but it is challenging due to the major surgical risk caused by these tumors' high vascularity ( 11 , 19 , 29 ). The efficacy of the surgical removal of a CPT can be considered as the single most determinant factor for long-term survival ( 19 ). In one human study, tumor recurrence was observed in 25% of patients ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation